A New Layer in a World Heritage Site: The Post-War Reconstruction of Mostar's Historic Core - Uluengin, Mehmet Bengu; Uluengin, Oze (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
This paper focuses on the historic core of Mostar in general, and the Old Bridge in particular, and attempts to trace this city's unique experience to rebuild and revitalize itself after a particularly destructive series of armed conflicts. Just as its preservation before the war was exemplary, Mostar's destruction during the painful dissolution of the Yugoslav Federation proved to be an example of human destruction at its worst. The city's devastation became a symbol of backwardness and ethnic strife in the Balkans. The destruction of the Old Bridge, in turn, came to be regarded as an attack on a multi-cultural Bosnia in general, and Mostar in particular with its Ottoman, Mediterranean and western-European architectural features. Mostar's postwar situation, particularly as it pertains to the city's architectural heritage, is considerably more complex than what many interpretations would have us believe. It seems that Mostar's (and by extension, Bosnia's) multiculturalism can be better understood if one accepts that some antagonism is necessarily present in any multicultural society. Indeed, greater insight into cities such as Mostar would be gained if they are taken not as sites of positive tolerance but those of competitive sharing and antagonistic tolerance. Methodologically, the study takes a panoptic view of numerous local and international institutions' efforts, and evaluates them based on the expectations and exigencies of local residents. The article's conclusions are articulated at several different, but interrelated levels: implications regarding the local populace, implications for cities that may have issues similar to that of Mostar, and lastly, implications for disciplines which focus on issues of urban regeneration, housing renovation, and the revitalization of old neighborhoods.
Keywords: Bosnia and Herzegovina; Mostar; Old Bridge; reconstruction; urban preservation; Architecture